2023
DOI: 10.1093/crocol/otad043
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Intestinal Ultrasound into an Inflammatory Bowel Disease Practice: How to Get Started

Abstract: Intestinal ultrasound (IUS) offers a safe, noninvasive, point-of-care tool for diagnosing and monitoring disease activity in patients with inflammatory bowel disease (IBD). IUS is used widely in Europe and Canada for IBD, but it remains underutilized in the United States. Growing interest in IUS in the United States has prompted many IBD centers to train their faculty in IUS. This, however, raises questions about how to effectively use this new tool in the United States, which does not use a social medicine mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…16 Furthermore, its diagnostic accuracy approaches that of more elaborate conventional radiological examinations like MRE. 17,18 It is worth noting that other studies have already demonstrated the efficacy of clinical decision-making involving IUS findings in reducing inflammation in patients with IBD, 19 and IUS is increasingly finding application in CD management, [20][21][22] underscoring its potential utility as a pivotal tool in striving for transmural remission. Inflammatory bowel disease gastroenterologists should be encouraged to consider transmural remission as a viable treatment goal for CD management.…”
mentioning
confidence: 99%
“…16 Furthermore, its diagnostic accuracy approaches that of more elaborate conventional radiological examinations like MRE. 17,18 It is worth noting that other studies have already demonstrated the efficacy of clinical decision-making involving IUS findings in reducing inflammation in patients with IBD, 19 and IUS is increasingly finding application in CD management, [20][21][22] underscoring its potential utility as a pivotal tool in striving for transmural remission. Inflammatory bowel disease gastroenterologists should be encouraged to consider transmural remission as a viable treatment goal for CD management.…”
mentioning
confidence: 99%